Using The Documentary Film “Sang Hyang Jaran: Teja Darmaning Kauripan” as A Medium For Preserving Traditional Art - I Nyoman Payuyasa; I Made Denny Chrisna Putra (Institut Seni Indonesia Denpasar, 2022)
Arts and culture make Bali one of the world's tourist destinations. At first glance, it seems that Balinese art and culture are holding up well. In fact, various media reports that several art forms have become extinct, such as the Sang Hyang dance, the baris kraras dance, the wayang wong dance, and so on. Even in Karangasem, there are ten traditional arts that have become extinct. In Badung Regency, there are fifteen types of culture that are almost extinct, as well as in Buleleng and Denpasar. It is very important to save endangered art forms by using audio-visual media, especially documentary films. There is a documentary that is very interesting to study, namely a documentary entitled